Phagocytosis of apoptotic cells - Henson, Peter (Henry Stewart Talks, 2007)
Apoptosis, Uptake of apoptotic cells, Specialized forms of phagocytosis, Efferocytosis, Anti-inflammatory and anti-immunogenic responses to apoptotic cells, Tissue cell deletion and replacement, Tissue homeostasis, Autoimmunity, fibrosis and emphysema